Designing an Online Sales System Using a Website - Latifah Hanum; Asyahri Hadi Nasyuha; Novica Irawati; Yustria Handika Siregar (Ali Institute or Research and Publication, 2024)
The rapid advancement of technology has significantly influenced the business landscape, pushing traditional businesses to adopt digital platforms to reach broader markets. This research focuses on the design and development of an online sales system (e-commerce) for Coffe ShopSipirok, a coffee shop looking to expand its market presence through a dedicated website. The e-commerce system is designed to enhance customer convenience, streamline purchasing processes, and provide detailed product information, ultimately aiming to increase sales and customer satisfaction. The development process includes requirements analysis, system design, implementation, and testing to ensure the website meets user needs and functions efficiently. The website features a user-friendly interface, secure payment gateway, and a responsive design adaptable to various devices. The implementation of this system not only improves the accessibility of Coffe Shop Sipirok's products but also positions the business competitively within the digital marketplace. Future work will involve continuous system upgrades and integration with advanced features such as customer feedback mechanisms and data analytics to further optimize the online shopping experience.